(untitled) (International Journal of Engineering and Computer Science, 2014)
Load balancing is a process of transferring load from one node to another to increase the performance of the whole system as each node is equally loaded in structure. The aim of this paper is to implement load balancing in hierarchical structure by taking different size of cluster at different level and compare its results with simple load balancing approach. The results show that our proposed hierarchical algorithm is more efficient than simple load balancing.